2016
DOI: 10.1016/j.neubiorev.2016.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain and behavior in adolescence: Findings from the Philadelphia Neurodevelopmental Cohort

Abstract: Sex differences in brain and behavior were investigated across the lifespan. Parameters include neurobehavioral measures linkable to neuroanatomic and neurophysiologic indicators of brain structure and function. Sexual differentiation of behavior has been related to organizational factors during sensitive periods of development, with adolescence and puberty gaining increased attention. Adolescence is a critical developmental period where transition to adulthood is impacted by multiple factors that can enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(124 citation statements)
references
References 120 publications
(139 reference statements)
9
115
0
Order By: Relevance
“…That is, amygdala–hippocampus connectivity, a connection most prominently influenced by sex, was stronger for boys than for girls, and hippocampal–ventral ACC connectivity was stronger for girls than for boys. Previous research on sex differences has mostly been done in adults (e.g., Alarcón, Cservenka, Rudolph, Fair, & Nagel, ; Kogler et al, ), and has shown higher hippocampal and/or amygdala connectivity in females than males, possibly related to their better memory performance (Gur & Gur, ). The sex differences we observed here may be an interesting starting point, but should be interpreted with caution until replicated, given the lack of consistent findings in prior developmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…That is, amygdala–hippocampus connectivity, a connection most prominently influenced by sex, was stronger for boys than for girls, and hippocampal–ventral ACC connectivity was stronger for girls than for boys. Previous research on sex differences has mostly been done in adults (e.g., Alarcón, Cservenka, Rudolph, Fair, & Nagel, ; Kogler et al, ), and has shown higher hippocampal and/or amygdala connectivity in females than males, possibly related to their better memory performance (Gur & Gur, ). The sex differences we observed here may be an interesting starting point, but should be interpreted with caution until replicated, given the lack of consistent findings in prior developmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…Girls enter puberty earlier than boys (Mul et al, ), and their brains also develop at a different pace during adolescence (Gogtay et al, ; Gur and Gur, ; Raznahan et al, ). Although puberty might in addition to age explain variance in brain development (Blanton et al, ; Brouwer et al, ; Menzies, Goddings, Whitaker, Blakemore, & Viner, ; review by Peper, Hulshoff Pol, Crone, & van Honk, ), we did not control for differences in pubertal timing.…”
Section: Discussionmentioning
confidence: 99%
“…Neural plasticity during adolescence is second only to infancy; this heightened plasticity may render the brain especially vulnerable to variation in environmental input during adolescence (Gee & Casey, 2015). Conceptualizing adolescence as an "organizational" period for the brain (Gur & Gur, 2016), researchers have posited that neurodevelopment during adolescence underlies the acquisition of complex skills involving executive function that are important for wellbeing in adulthood (Aoki, Romeo, & Smith, 2017). Given the sensitivity of the adolescent brain and the potentially cascading consequences of deviations in neurodevelopment, it is important to characterize more precisely the associations between SES and brain volume during this period.…”
mentioning
confidence: 99%
“…Although studies of the neural correlates of SES typically "control" statistically for the biological sex of participants (i.e., by holding sex constant in predictive models), researchers rarely test sex as a moderator of SES and brain structure. The confluence of sex differences in neurodevelopment (Dennison et al, 2013;Gur & Gur, 2016;Wierenga, Langen, Oranje, & Durston, 2014;Wierenga, Sexton, Laake, Giedd, & Tamnes, 2018) and in sensitivity to environmental input Jaffee, Caspi, Moffitt, Polo-Tomás, & Taylor, 2007;Whittle et al, 2014Whittle et al, , 2017 may lead to sex differences in the corresponding to family size. Given wide variation in cost of living across the United States, the same income in different geographic areas may not reflect equivalent economic wellbeing.…”
mentioning
confidence: 99%
See 1 more Smart Citation